Dewatering of waste lime mud and after calcining its applications in the autoclaved products. (1st February 2016) - Qin, Juan; Cui, Chong; Yang, Chuanmeng; Cui, Xiaoyu; Hu, Biao; Huang, Jiantao
Abstract: Lime mud from papermaking process (LMP) as a toxic industrial waste has high moisture content. Fly ash and cement aided dewatering of LMP was developed and the best efficiency was obtained when fly ash and cement were added simultaneously. The dewatered LMP was calcined at different temperatures to prepare lime. Available lime content and crystalline phases were detected. Mixtures of LMP and cement presented the highest available lime content. After calcining at 800–1200 °C, mixtures of 90 wt % LMP and 10 wt % fly ash contained lime (CaO) and dicalcium silicate (β-Ca2 SiO4 ) as the major phases. The application performance of the prepared lime was investigated by using it in the autoclaved products and the results showed that autoclaved products with high strength were obtained and they were green building materials.